Analisis Metode Forward Chaining pada Sistem Pakar: Systematic Literature Review - Anisa Maulida; Arisky Rahmatulloh; Irwan Ahussalim; Robby Alvian; Perani Rosyani (Shofanah Media Berkah, 2023)
Information technology, which is currently growing rapidly, has now been used in various fields, including psychology, education, agriculture, and health. This motivates professionals to continue building computers with the goal of helping people or even outperforming them. Computer programs called expert systems are created to emulate the knowledge and skills of a human expert on a particular topic. The main goal of an expert system is to offer answers or suggestions that are comparable to those made by human experts. The forward chaining method is one method that can be used to develop expert systems. The decision-making approach known as